Rehabilitation following shoulder arthroplasty in the United Kingdom National Health Service: A survey of publicly facing information - Littlewood, Chris; Morgan, Marie; Pitt, Lisa; Moffat, Maria; Edwards, Peter; Davies, Ronnie; Peach, Chris (Wiley-Blackwell, 2020)
Introduction: The prevalence of shoulder arthroplasty (SA) is rising, but there is limited research evaluating rehabilitation following SA and whether there is an optimal approach remains unknown. The aim of this study was to understand current National Health Service (NHS) practice for rehabilitation following SA as a platform for conducting much needed further research. Methods: Two reviewers independently undertook electronic searches for publicly available information sheets (PIS) from websites of NHS Trusts that included detail about rehabilitation following SA, for example, duration of immobilisation. One reviewer extracted data, and a second reviewer verified this. Ethical approval: Not required. Results: Forty‐three PIS from 40 Trusts were identified. Twenty‐four referred to more than one type of arthroplasty (anatomic, reverse and hemiarthroplasty) but did not describe different approaches to rehabilitation based on prosthesis type. Twenty‐five PIS provided some instruction regarding movement restrictions, which varied considerably. All PIS referred to postoperative immobilisation, typically with a sling, with median duration of 4 weeks (range 0 to 8). Thirty‐four PIS reported commencing passive exercise immediately. Median time to commencing active exercise was 4 weeks (range 1 to 6) and 5 weeks (range 1 to 16) for resisted exercise. Median time expected to return to driving was 6 weeks (range 3 to 12) and general work 12 weeks (range 3 to 26). Conclusion: This study has highlighted significant heterogeneity between rehabilitation approaches following SA, not previously reported in the United Kingdom, with a lack of specific rehabilitation PIS for different prosthesis types. Our results will facilitate evaluation of rehabilitation strategies in future research.